Laboratory manual - K Smith (Harcourt Brace Jovanovich, 1980)
The book presents some aspect of the physical world in a more controlled, analyzes Newton's laws of motion as they apply to the objects, recognizes the peculiar nature of magnetic force. The book also deals with frictionless air bearings, hilden details of motions by multiple flash photography, or an oscilloscope of electricity